ESTROGEN EFFECT ON WISTAR'S VAGINAL EPITHELIUM - Surur, Abu; Sugandi, Suwandi; Haroen, Zulhardi; Noegroho, Bambang S; Tjahjodjati, Tjahdjojati; Safriadi, Ferry; Siregar, Safendra; Adriansjah, Ricky; Adi, Kuncoro; Hernowo, Betthy S (Indonesian Urological Association, 2010)
Objective: To evaluate the effect of estrogen on wistar’s vaginal epithelium. Material & method: We divided 30 female wistars into three groups, ten wistars underwent bilateral ovariectomy, 10 wistars underwent bilateral ovariectomy, and estrogen replacement and 10 wistars as control. The second group received estradiol 1 mg/kg/day, directly after ovariectomy. After 4 weeks the vagina was then harvested and stained with hematoxylin-eosin to evaluate the thickness of epithelial layer of vagina. A pair T-test was use for statistical analysis. Results: Estrogen ablation decreased the thickness of epithelial layer in wistar’s vagina. The mean thickness of epithelial layer in vagina were 3, 5, and 10 for each group respectively. The mean epithelial layer of the first group as well as the second group showed significant difference compared to control group (p>0,05), while the first group showed insignificant difference compared to the second group. Conclusion: Estrogen ablation seems to decrease the thickness of vaginal epithelium, while estrogen replacement revealed insignificant effect.